The Cardiac pathophysiology of Covid-19 - Daisley, Hubert; Acco, Oneka; Joseph, Haille; Daisley, Johann; Daisley, Martina (Brazilian Journal of Case Reports, 2024)
The heart is a key target organ in SARS-CoV-2 infection. During the illness stage of acute Covid-19, fibrin thrombi frequently form within the coronary microcirculation, including the vasa vasorum. These thrombi are predominantly located in the abluminal spaces, the sites of pericyte location, of the vessel wall, in both the microvascular and epicardial vessels. A hallmark histopathological finding is the presence of diffuse, focal fibrin deposits surrounding myocardial fibres, which exhibit varying degrees of degeneration and atrophy. This process contributes to myocardial injury, which is reflected both biochemically and clinically in the acute and long-term phases of Covid-19. Myocardial fibrosis results from this pathological cascade, without a concurrent cellular inflammatory response associated with the myocardial stromal fibrin deposits. During the convalescent stage of acute Covid-19, focal myocardial fibrosis and the presence of thrombi within myocardial vessels remain apparent but sparse. Vascular changes, such as fibrin thrombi within the cardiac microcirculation, exhibit similarities to those observed in the pulmonary microcirculation in Covid-19. In Covid-19, the vascular findings of fibrin thrombi deposits within the cardiac micro vascular circulation are like those seen within the pulmonary microcirculation.